1998
DOI: 10.1161/01.atv.18.11.1698
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Platelet α IIb β 3 by Oxidants Is Associated With Tyrosine Phosphorylation of β 3

Abstract: Abstract-Reactive oxygen species play an important role at the site of vascular injuries and arterial thromboses. We studied the mechanism mediating platelet aggregation induced by H 2 O 2 , a major cellular oxidant. Exposure to H 2 O 2 triggered platelet aggregation, but only when the platelets were stirred. Strong platelet aggregation induced by H 2 O 2 required the presence of the tyrosine phosphatase inhibitor sodium orthovanadate (NaVO 4 ) and was dependent on the participation of integrin ␣ IIb ␤ 3 (glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 46 publications
(60 reference statements)
0
13
0
1
Order By: Relevance
“…Tyrosine phosphorylation of GPIIIa (regulatory subunit of the classical platelet fibrinogen receptor) after thrombin-induced platelet aggregation occurs. Irani et al (1998) found that GPIIIa was phosphorylated on tyrosine also in platelets exposed to H 2 O 2 . In the platelet aggregation induced by free radicals, tyrosine kinase pathways are involved, and it seems that p72 syk may be an important kinase in tyrosine phosphorylation of phospholipase C (Nagai et al 1994).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tyrosine phosphorylation of GPIIIa (regulatory subunit of the classical platelet fibrinogen receptor) after thrombin-induced platelet aggregation occurs. Irani et al (1998) found that GPIIIa was phosphorylated on tyrosine also in platelets exposed to H 2 O 2 . In the platelet aggregation induced by free radicals, tyrosine kinase pathways are involved, and it seems that p72 syk may be an important kinase in tyrosine phosphorylation of phospholipase C (Nagai et al 1994).…”
Section: Discussionmentioning
confidence: 97%
“…H 2 O 2 enhances platelet aggregation induced by phospholipid-derived arachidonate. Several reports indicate a role of ROS in regulation of tyrosine phosphorylation in platelet proteins by inhibiting phosphatase(s) (Hernandez-Hernandez et al 1999;Irani et al 1998). Tyrosine phosphorylation of GPIIIa (regulatory subunit of the classical platelet fibrinogen receptor) after thrombin-induced platelet aggregation occurs.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are intimately involved in the process of oxidative metabolism, the process by which platelets obtain the majority of their energy supply when stored under ideal ex vivo conditions [33]. Hydrogen peroxide has also been shown to trigger platelet aggregation [17,19,34,35], as well as inhibit aggregation, depending on the presence of other mediators, such as NO and the type of agonists used [36]. ROS may also play a role in the generation of platelet microparticles and subsequent procoagulant effects [37] as well as in regulating tyrosine phosphorylation of many key proteins involved in platelet signal transduction, including vasodilator-stimulated phosphoprotein (VASP) [34,38].…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen peroxide has also been shown to trigger platelet aggregation [17,19,34,35], as well as inhibit aggregation, depending on the presence of other mediators, such as NO and the type of agonists used [36]. ROS may also play a role in the generation of platelet microparticles and subsequent procoagulant effects [37] as well as in regulating tyrosine phosphorylation of many key proteins involved in platelet signal transduction, including vasodilator-stimulated phosphoprotein (VASP) [34,38]. Similarly, increased metabolism, a reduced ability to aggregate in response to agonists, and increased expression of platelet signaling proteins, including VASP, have been observed in Mirasol- treated platelets [5,9,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…apoptosis) 62,70 . In the future, it will be important to determine what factors and mechanisms control aerobic respiration because lactate production is greater in platelets derived from aged (reproductively senescent) compared with younger (reproductively competent) individuals 71,72 and to determine whether hormonal status affects energy pathways independent of chronological age.…”
Section: Theories Of Ageing Oestrogen and Platelet Functionsmentioning
confidence: 99%